PENGARUH PENGALAMAN AUDIT, BEBAN KERJA, TASK SPECIFIC KNOWLEDGE TERHADAP PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN (Studi pada KAP di Sumatera Bagian Selatan) - HASNI YUSRIANTI (Program Studi Magister Manajemen FE Unsri, 2015)
The purpose of this study is to determine, obtain empirical evidence and analyze the effect of audit experience, workload, and task-specific knowledge on fraud detection of financial statements. The data used is questionnaires to Auditor (senior and junior auditors) in 14 (fourteen) Public Accounting Firm (KAP) in Southern Sumatra, which is located at: Palembang city, Jambi, Bengkulu, Lampung and Bangka Belitung Province. Independent variable is audit experience, workload, task specific knowledge, while the dependent variable is fraud detection of financial statements. The analysis technique used is multiple regression analysis, while the hypotheses test performed simultaneously and partially after the regression model free of classical assumption violations.The results showed that audit experience, workload and task specific knowledge both partially and simultaneously have a positive influence on fraud detection on financial statements. The coefficient of determination (R2) is 0.893 that means the independent variable auditor experience, workload and task specific knowledge affecting on fraud detecting on financial statements of 89.3% and the remaining of 10.7% is influenced by other variables that is not included in this research.